An Analysis on Forms and Functions of Code-Switching and Code-Mixing Used in Drama Performance - Shafira Annisa Masruroh; Setia Rini (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
The study was conducted in order to describe the forms and the functions of code-switching and code-mixing in drama performance of ALE of the students of ICP batch 2017. The study was descriptive qualitative research. The data are collected by observation and documentation in the drama performance in Art and Language Exhibition ‘Prahara Ing Argabelah’. The finding shows that 24 unit analysis of code-switching found 6 used tag-switching, 15 used inter-sentential switching, and 3 used intra-sentential switching. Furthermore, 27 unit analysis of code-mixing performed 21 intra-sentential code mixing, 5 intra-lexical code mixing, and 1 involving a change of pronunciation. Then, from 24 unit analysis of code-switching, the researcher found six functions in the drama conversation. There are 6 addressee specifications, 2 repetitions, 7 interjections, 1 message qualification, 2 personalization and objectivizations, and 6 facilities of expression. Moreover, the researcher just found 3 functions from 27 unit analysis of code-mixing. There are 1 repetition, 2 message qualifications, and 24 facilities of expression.